The persisting conditions of ‘Day Zero’: How chronic crisis challenges media narratives about the Cape Town water crisis - Mihalopoulos, Kyra (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.